Analysis of the Kampus Mengajar Program Cohort 7 on the Improvement of Literacy and Numeracy Abilities of Students at SD Negeri 1 Margototo - Rita Sari, Wiwin; Setyawati, Astri; Astuti, Dwilita (International Journal of Business, Law, and Education, 2024)
The Kampus Mengajar program, part of the Merdeka Belajar-Kampus Merdeka (MBKM) initiative, enables university students to engage in primary education, particularly in areas with limited access. This study analyzes the impact of the seventh cohort of the program on literacy and numeracy skills at SD Negeri 1 Margototo. Using a qualitative case study approach, data were gathered through observations, interviews, and documentation from teachers, students, and participating university students. The research findings indicate that there was an increase in the average scores from the pretest and post-test of the Minimum Competency Assessment (AKM), specifically a 42% improvement in literacy skills and a 44% improvement in numeracy skills. These findings suggest that the Kampus Mengajar program plays a significant role in enhancing the quality of primary education and serves as an effective collaborative model between university students and schools in underserved areas.